Weak coordination among petiole, leaf, vein, and gas‐exchange traits across Australian angiosperm species and its possible implications. Issue 1 (29th December 2015) - Gleason, Sean M.; Blackman, Chris J.; Chang, Yvonne; Cook, Alicia M.; Laws, Claire A.; Westoby, Mark
Abstract: Close coordination between leaf gas exchange and maximal hydraulic supply has been reported across diverse plant life forms. However, it has also been suggested that this relationship may become weak or break down completely within the angiosperms. We examined coordination between hydraulic, leaf vein, and gas‐exchange traits across a diverse group of 35 evergreen Australian angiosperms, spanning a large range in leaf structure and habitat. Leaf‐specific conductance was calculated from petiole vessel anatomy and was also measured directly using the rehydration technique. Leaf vein density (thought to be a determinant of gas exchange rate), maximal stomatal conductance, and net CO2 assimilation rate were also measured for most species ( n  = 19–35). Vein density was not correlated with leaf‐specific conductance (either calculated or measured), stomatal conductance, nor maximal net CO2 assimilation, with r 2 values ranging from 0.00 to 0.11, P values from 0.909 to 0.102, and n values from 19 to 35 in all cases. Leaf‐specific conductance calculated from petiole anatomy was weakly correlated with maximal stomatal conductance ( r 2  = 0.16; P  = 0.022; n  = 32), whereas the direct measurement of leaf‐specific conductance was weakly correlated with net maximal CO2 assimilation ( r 2  = 0.21; P  = 0.005; n  = 35). Calculated leaf‐specific conductance, xylem ultrastructure, and leaf vein density do not appear to be reliable proxy traits for assessing differences in rates of gas exchange or growth across diverse sets of evergreen angiosperms. Abstract : Quantifying the relationship between water transport through plants and rates of photosynthesis are important for many process‐based growth models. Such models are presently being used to predict plant growth and growth response to changes in climate (e.g., precipitation and temperature). A positive correlation between water transport (obtained from anatomical measurements) and photosynthesis is most often assumed. Our data suggest that careful consideration should be given before using anatomic data (e.g., vessel dimensions, estimated rates of conductance, vein density) as proxy measurements for rates of stomatal conductance, CO2 assimilation, or growth.